Kepatuhan Wajib Pajak Pada Masa Pandemi Covid 19: Ditinjau Dari Slippery Slope Framework - Endang Dwi Wahyuni; Annida Utami Putri; Driana Leniwati (Jurnal Reviu Akuntansi dan Keuangan, 2022)
This study aims to find empirical evidence of the influence of Slippery Slope Framework that is measured by the trust in tax authorities and the influence of the power of tax authorities on taxpayer compliance during the covid-19 pandemic. The data were obtained from corporate taxpayers registered with Tax Service Office (KPP) Pratama Batu in November – December 2021. The sampling was determined by using purposive sampling technique and the research instrument used questionnaire technique. The data analysis method used is PLS-SEM with 47 corporate taxpayers as samples. The results show that the compliance of corporate taxpayers registered with KPP Batu during the Covid 19 pandemic was quite good, while the results of hypothesis testing is that the power of the tax authorities had a significant positive effect on taxpayer compliance, while trust in the tax authorities had no effect on taxpayer compliance.